DILEMATISM: PRINCIPAL’S MANAGERIAL STRATEGIES IN REALIZING THE COVID-19 VACCINATION PROGRAM IN ELEMENTARY SCHOOL - Hamna, Hamna; BK, Muh. Khaerul Ummah (Universitas Madako Tolitoli, 2021)
The factor of guaranteeing safety from the dangers of Covid-19 will affect the accessibility of children's education services in elementary schools. This study aims to reveal the facts behind the role of school principals in an effort to realize government policies related to the Covid-19 vaccination program in elementary schools which are still reaping controversy among parents/guardians of students. The research approach used is a qualitative descriptive expost facto analysis with research respondents including principals at the elementary school level/equivalent throughout the district. Tolitoli and parents/guardians of students. The focus of the research specifically covers all private schools at the elementary/equivalent level in Kab. Tolitoli, totaling 26 schools. The results showed: (a) There were 12 schools that had socialized the vaccination policy in their education units (46.15%); (b) There are 8 schools that are still in doubt (30.77%); and (c) There are 6 schools that have not socialized (23.08%). The strategies implemented by the school principal include: (1) a strategy for socializing the safe Covid-19 vaccination program by presenting the principal and his staff, medical personnel, and parents/guardians of students; (2) Situation analysis and evaluation of safe vaccination programs for children; (3) The principal as a motivator. The dilemma of the level of distrust of parents/guardians of the safety guarantee for the effectiveness of their child's vaccination is 88.73% taking into account the character of the child being underage and 11.27% responding favorably to the implementation of the policy